Serahsi’ de kazai hüküm- diyani hüküm ayrımı - Demiray, Mustafa (My University, 2001)
Bu çalışma İmam Serahsi'nin hacimli eseri el-Mebsut'un Kitabu't-Talak bölümünden hareketle İslam hukukunda ahlaki-dini hükümler ile yargı hükümleri arasındaki ayrılığı incelemeyi hedefliyor. Hükümler, toplumun hukuki açıdan istikrarlı işleyebilmesini de göz önünde bulundurur. Buna bağlı olarak kadının uyacağı usuller, dikkate alacağı deliller belirlenmiştir. Kadı tarafların kadı önünde çözüme bağlamayı tercih ve mürafaa ettikleri meseleleri objektif şekilde çözmekle görevlidir. Davada olayın iki taraflı olması sebebiyle yeni bir nizaya sebebiyet vermemek, taraflardan birinin meyl ithamından ve Allah katında sorumluluktan kurtulmak için ancak zahire göre, yani delillerle ispatlanan ve hallerin delalet ettiği şeylere göre hükmedilir. Kadının hükmü taraflar açısından bağlayıcıdır. Kadı, talak lafzını bir bağdan boş olmak anlamında kullanan kişinin eşinin boş olduğuna hükmeder. Lafzın bu anlama muhtemel olmasını ve kişinin niyetini, ancak -kocanın bu sözü, karısının ellerini çözdükten sonra söylemesi gibi- bir karinenin delaleti halinde dikkate alır. Bir karine yoksa niyeti dikkate almaksızın zahire göre ve lafzın mucebiyle, yani boşanma anlamıyla hükmeder. Oysa müfti kişinin beyanına itibar eder, onun niyetini dikkate alır ve lafzın mucebine göre bu durumdaki bir kişi için geçerli olan hükmü bildirir. Kişiyi bu fetvaya uyup uymama konusunda kendisine karşı sorumlu olduğu asıl zat olan Allah ile başbaşa bırakır. Kişi lafzı ve niyeti konusunda doğru bilgi vermişse hüküm diyaneten / kendisiyle Allah arasındaki hususta da öyledir. Aksi halde, kendi yanlış bilgilendirmesine göre verilen fetva onu diyaneten sorumluluktan kurtarmaz. Bu durumda kadının hükmünden kazaen ve kazai hüküm, müftinin hükmünden de diyaneten ve diyani hüküm olarak bahsedilir. Kazai hüküm - diyani hüküm ayrımı sarih beyan, kinai beyan, amm lafız, umumda tahsis, mutlakın takyidi, müşterek lafız, lafzın muceb ve muhtemeli, niyet ve irade teorileri gibi bir takım usul-ı fıkıh konularına dayanır. Bizim Serahsi'nin eserinde araştırdığımız bu konu, onun eserinin dayandığı temel kaynak olan İmam Muhammed'in eserlerinde de aynı ifade kalıplarıyla işlenmektedir.

This study explores the distinction between ethical-religious (diyanî) and juridical (kazaî) convictions in Islamic law with special emphasis on Kitab al-Talaq of Imam al-Sarakhsî's voluminous work al-Mabsut. Islamic judicial convictions consider, among others, stability in social life, and therefore the kinds of evidence a kadi uses in making his decisions, as well as the ways in which this evidence is processed are determined in Islamic law. In this context, kadi's task is to solve objectively the problems brought up in front of him by the parties of a particular case. He makes his decisions on the basis only of zahir, i.e. things supported by relevant evidence and pointed out by the situation in order to prevent the emergence of a new dispute, and to be able to escape from the possible accusations addressed by either party, and from responsibility in the eyes of Allah. Consequently, kadi's conviction has a compulsory character for both of the parties. If, for instance, a person uses the word talaq in the sense of being free from any tie, the kadi decides on the divorce of that person. He takes into account this meaning and the intention of that person only in the presence of an evidence indicating, for example, that a husband uters this word after he untied his wife's hands. However, if such an evidence does not exist, the kadi decides on the basis of zahir and what the individual utterence denote, that is, in the sense of divorce. The müfti, on the other hand, determines the valid decision for such a situation taking into account the person's intention and decleration, as well as the denotation of an utterence. In doing so, he leaves the person alone with Allah, to whom he or she is responsible for obeying the consequence of this fetva. The conviction becomes true also diyanatan, in ethico-religious terms, that is, in the situation between him/ her and Allah, on the condition that the person demanding the fetva gives correct information about both his or her decleration and intention. Otherwise, the fetva offered to a person according to wrong information he or she provides does not remove his or her responsibility diyanatan, even if this person becomes innocent kazaan. Within this framework, the conviction that is given by the kadi is called kazaî and kazaan, and the one offered by the müfti is called diyanî and diyanatan. The distinction between ethical-religious (diyanî) and juridical (kazaî) convictions in Islamic law is based on a number of concepts in usul al-fiqh, Islamic juridical methodology, including those of sarih, kinaî, amm, takhsis, takyid, müshtarak, mucab and muhtamal, as well as the theories of will and intention. The distinction between ethical-religious and juridical convictions can also be found in earlier legal literature, for example, in various works of Imam Muhammad, whose account is the basic source to which Sarakhsi refers on the basis of whose work this study analyzes the issue.
Keywords: Din; Fıkıh ve fıkıh ilmi; HUKUK-İSLAM HUKUKU; İslam Dini; İslam Hukuku